2011
DOI: 10.1097/jnn.0b013e3182029846
|View full text |Cite
|
Sign up to set email alerts
|

Parental Coping and Childhood Epilepsy

Abstract: Parents of children with epilepsy, like parents of children with many other chronic conditions, are faced with a constant feeling of uncertainty about their child's condition. This uncertainty can lead to a decreased ability to cope as evidenced by increased stress levels, negative mood states, and impaired family functioning. Because altered coping in the parent may have a profound negative impact on the child's psychosocial adjustment to living with a chronic condition, it is important to identify ways to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 36 publications
(57 reference statements)
3
35
0
1
Order By: Relevance
“…Two of these scales, Role Restriction and Spouse, are part of the seven subscales constituting the so-called Parent domain, which reflects feeling inadequate for one's parenting task. This may be understood from the fact that seizures are, in the majority of cases, unpredictable, which induces uncertainty in parents [6] and a tendency to watch their child all the time to ensure his safety. Moreover, the feeling that fatigue and stresses and strains in the child may induce seizures [23] renders many parents less eager to go on family trips with this child, let alone to undertake spontaneous activities with this child or go out together and leave the child with a sitter.…”
Section: Prior To Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these scales, Role Restriction and Spouse, are part of the seven subscales constituting the so-called Parent domain, which reflects feeling inadequate for one's parenting task. This may be understood from the fact that seizures are, in the majority of cases, unpredictable, which induces uncertainty in parents [6] and a tendency to watch their child all the time to ensure his safety. Moreover, the feeling that fatigue and stresses and strains in the child may induce seizures [23] renders many parents less eager to go on family trips with this child, let alone to undertake spontaneous activities with this child or go out together and leave the child with a sitter.…”
Section: Prior To Surgerymentioning
confidence: 99%
“…Childhood epilepsy, particularly pharmacologically intractable epilepsy, is a risk factor par excellence for parenting stress [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Within the pediatric epilepsy literature, several interventions incorporating both children and their families have been reported. 40 These interventions aimed to increase medical knowledge about epilepsy, as well as educate families about the management of their children's symptoms. 40 Three studies reported a postintervention increase in parent and child knowledge [41][42][43] ; two resulted in improved family functioning 42 or parental anxiety 44 ; two reported no impact on level of caregiver depression or anxiety 43,45 ; and one was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…40 These interventions aimed to increase medical knowledge about epilepsy, as well as educate families about the management of their children's symptoms. 40 Three studies reported a postintervention increase in parent and child knowledge [41][42][43] ; two resulted in improved family functioning 42 or parental anxiety 44 ; two reported no impact on level of caregiver depression or anxiety 43,45 ; and one was not evaluated. 46 Beyond educating parents about the management of their children's epilepsy, our findings suggest that the implementation and evaluation of family centered care practices that address caregiver well-being and provide linkages to supportive community resources may result in more promising HRQL for children and families.…”
Section: Discussionmentioning
confidence: 99%
“…This uncertainty can lead to a decreased ability to cope as evidenced by increased stress levels, negative mood states, and impaired family functioning. Because altered coping in the parent may have a profound negative impact on the child's psychosocial adjustment to living with a chronic condition, it is important to identify ways to facilitate positive coping skills in the parent (Duffy, 2011).…”
Section: Childhood Epilepsy and Familymentioning
confidence: 99%